ETIKA DAN PERBEDAAN INTENSITAS PENGGUNAAN FACEBOOK BERDASARKAN TIPE KEPERIBADIAN, RELIGIUSITAS DAN GENDER: SEBUAH KAJIAN KONSEPTUAL - Suliyanto . (Fakultas Ekonomi Universitas Pekalongan, 2015)
The use of social networking is growing quickly in recent years. One of the most popular social network inIndonesia is facebook. The development of the use facebook on one hand a positive impact on the other, alsogive a negative impact.Research linking between religiosities, personality and gender to ethics and the intensity of a relationship havebeen carried out but these studies are generally carried out in the real world, therefore the number of ethicalissues and the intensity of the use of facebook to do research on ethics and intensity of use based on personalityreligiosities and gender.Keywords: Ethic, intensity of relationship, personality, gender, religiosity